Effect of pipe rotation on flow pattern and pressure drop of horizontal two-phase flow. (February 2019) - Baghernejad, Yosef; Hajidavalloo, Ebrahim; Hashem Zadeh, Seyed Mohsen; Behbahani-Nejad, Morteza
Highlights: Effect of pipe rotation on horizontal two-phase flow patterns was experimentally investigated. In a horizontal pipe, Stratified Wavy region starts at lower VSG as pipe rotation increases. In a 10° inclined pipe, Stratified Wavy region appears and enlarges as pipe rotation increases. Annular flow regime enlarges with increasing pipe rotational speed. Pressure drop increases as the pipe rotational speed increases. Abstract: In this paper, the effect of pipe rotation on two-phase flow patterns and pressure drop of a horizontal pipe is experimentally investigated. To obtain two-phase flow patterns and related transition boundaries, a unique experimental set-up was constructed to measure flow patterns under different pipe rotational speeds. A Plexiglas pipe, with 4000 mm length and 25.4 mm ID was used in experiments to allow direct observation of flow pattern. For rotation of the pipe, an electromotor coupled with gearbox was used to allow different rotational speeds. The set-up also supports up to ±25° inclination. Air and water were used as the gas and liquid phase, respectively. Over 3800 experiments were conducted to draw flow pattern maps at six different rotational speeds of 0, 50, 100, 200, 300 and 400 rpm in both horizontal and 10° inclined pipe. To validate the results, experimental findings were compared with previous research for a horizontal fixed pipe case. Results show that pipe rotation has a significant effect on the flow pattern map and the transition boundaries. It was found that in horizontal pipe case, the stratified smooth flow regime decreases as the pipe rotation increases and disappears at high revolution speeds. Moreover, the annular regime enlarges with increasing pipe rotational speed. For a 10° inclined pipe, the stratified wavy region appears as the pipe rotation speeds up. It was observed that for both horizontal and inclined pipe, pressure drop considerably increases as the pipe rotational speed increases. Furthermore, the effect of pipe inclination on the pressure drop is reduced as the rotational speed increases.